The social weeks of the Peruvian Church under the light of Caritas in Veritate: the case of the first social week in 1959. - Elgegren Reátegui, Fernando (2010)
Pope Benedict XVI, in his encyclical letter Caritas in Veritate, makes it very clear that “The Christian vocation to development helps to promote the advancement of all men and of the whole man”(CIV.18), an approach that - as the Pope says –is also supported by Pope Paul VI in his encyclical letter Populorum Progressio, and Pope John Paul II’s Centesimus Annus. The author, as member representing UNIFE before Peru’s Episcopal Commission for Social Action (CEAS), participates in the research performed by the catholic universities of our country on the influence and intervention of the church in Peruvian society in recent decades.This article relates the progress of research on the study of the Social Weeks in Peru with the approaches proposed in the Caritas in veritate.